Talcott Parsons’ Sociological Perspective In Viewing Social Change In Society In The New Normal Era - Endah Ratnawaty Chotim (HK-Publishing, 2022)
AbstractThis study aims to see the various changes that occur in people’s daily lives in the new normal era due to the impact of the pandemic in multiple parts of the world. In looking at this phenomenon, a sociological perspective will be used based on the functionalism theory that Talcott Parsons has coined. This research will use a qualitative approach that uses various previous studies and studies as the source. The results of the study found that the multiple changes that occurred in the new normal era in society had become a discussion that was quite widely discussed. This is because the covid pandemic has had many negative impacts on all levels of society, so efforts to suppress the virus and its effects are always discussed. Meanwhile, Parsons argued long ago that a new social system could be formed through 4 keys, namely adaptation, goal attainment, integration, and latency (AGIL). The new normal era can be adequately achieved through these four keys without any difficulties that will hinder it.Keywords: New Normal, Social Change, Talcott Parsons. AbstrakPenelitian ini bertujuan untuk melihat berbagai perubahan yang terjadi dalam kehidupan sehari-hari masyarakat di era new normal akibat dampak pandemi di berbagai belahan dunia. Dalam melihat fenomena ini akan digunakan perspektif sosiologis berdasarkan teori fungsionalisme yang dicetuskan Talcott Parsons. Penelitian ini akan menggunakan pendekatan kualitatif yang menggunakan berbagai penelitian dan penelitian terdahulu sebagai sumbernya. Hasil penelitian menemukan bahwa berbagai perubahan yang terjadi di era new normal di masyarakat menjadi perbincangan yang cukup ramai diperbincangkan. Hal ini dikarenakan pandemi covid telah banyak memberikan dampak negatif pada semua lapisan masyarakat, sehingga upaya untuk menekan virus dan dampaknya selalu dibahas. Sementara itu, Parsons sejak lama berpendapat bahwa sistem sosial baru dapat dibentuk melalui 4 kunci, yaitu adaptasi, pencapaian tujuan, integrasi, dan latensi (AGIL). Era kenormalan baru dapat dicapai dengan baik melalui keempat kunci ini tanpa ada kesulitan yang menghalanginya.Kata kunci: New Normal, Perubahan Sosial, Talcott Parsons.